2015
DOI: 10.1080/14765284.2015.1090267
|View full text |Cite
|
Sign up to set email alerts
|

The effects of corporate governance and ownership on the innovation performance of Chinese SMEs

Abstract: We investigate the degree to which corporate governance and ownership affect the innovation performance of firms in China with a particular focus on privately owned small and medium enterprises (SMEs). Using the appropriate theoretical frameworks, we derive hypotheses regarding the impact of ownership concentration, board size and composition, and the background of the CEO on innovative activity. These hypotheses are tested using a unique sample of 370 mostly private and relatively small Chinese firms in Zheji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 121 publications
10
94
0
13
Order By: Relevance
“…By examining Chinese listed firms for 2001-2004, Choi et al (2011 find that foreign ownership and business affiliation are positively related to firm patenting. In a similar vein, Shapiro et al (2015) investigate small and medium enterprises (SMEs) in China and find that corporate governance and ownership are significantly associated with firm patenting. So far, the causality is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…By examining Chinese listed firms for 2001-2004, Choi et al (2011 find that foreign ownership and business affiliation are positively related to firm patenting. In a similar vein, Shapiro et al (2015) investigate small and medium enterprises (SMEs) in China and find that corporate governance and ownership are significantly associated with firm patenting. So far, the causality is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Table contains the mean, standard deviation, and correlations for each variable. The mean value of ownership concentration was 49.51%, which is typically regarded as highly concentrated (Shapiro et al, ). Trust was not significantly related to radical innovation, but the square of trust had a significantly negative correlation with radical innovation.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Previous research has found that ownership concentration influences firm innovation outcomes (Shapiro et al, ). Thus, we asked the respondents about the proportion of shares held by their firm's largest shareholder and eight firms were excluded from our analysis because their largest shareholder held less than 10% of their shares (Claessens et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations